Selectivity of bovine interleukin-2 mutein stimulation on bovine peripheral blood mononuclear cells - MITOMA, Shuya; UTO, Tomofumi; FUKAYA, Tomohiro; TOMINAGA, Moe; SEKIGUCHI, Satoshi; SATO, Katsuaki; NORIMINE, Junzo (Journal of Veterinary Medical Science, 2025)
Delivery of engineered interleukin-2 (IL-2) variants (muteins) is thought to be a promising cancer therapy in humans and mice. Our previous study indicated that bovine IL-2 (boIL-2) has a great potential to elicit NK cell activity for which distribution of IL-2 receptors on the target cell surface influences signal transduction. We developed nine boIL-2 muteins and examined the influence of the muteins on bovine peripheral blood mononuclear cells in vitro. On bovine peripheral mononuclear cells, NK cells strongly expressed CD122, followed by CD8+ T cells, while CD4+ T cells and γδ T cells did not show significant CD122 expression. All boIL-2 muteins showed decreasing in binding to boIL-2 receptor α, CD25, while maintaining their ability to bind to boIL-2 receptor βγ, CD122/CD132, heterodimer. The mutein F44A and E63A suppressed CD4+ T cell expansion but maintained the NK cell expansion. These results indicate that boIL-2 muteins can alter immunological outcomes and may be used for clinical intervention for a disease progression.